Disparities in accessibility to evidence‐based breast cancer care facilities by rural and urban areas in Bavaria, Germany. Issue 13 (7th April 2021) - Stangl, Stephanie; Rauch, Sebastian; Rauh, Jürgen; Meyer, Martin; Müller‐Nordhorn, Jacqueline; Wildner, Manfred; Wöckel, Achim; Heuschmann, Peter U.
Abstract : Background: Breast cancer (BC), which is most common in elderly women, requires a multidisciplinary and continuous approach to care. With demographic changes, the number of patients with chronic diseases such as BC will increase. This trend will especially hit rural areas, where the majority of the elderly live, in terms of comprehensive health care. Methods: Accessibility to several cancer facilities in Bavaria, Germany, was analyzed with a geographic information system. Facilities were identified from the national BC guideline and from 31 participants in a proof‐of‐concept study from the Breast Cancer Care for Patients With Metastatic Disease registry. The timeframe for accessibility was defined as 30 or 60 minutes for all population points. The collection of address information was performed with different sources (eg, a physician registry). Routine data from the German Census 2011 and the population‐based Cancer Registry of Bavaria were linked at the district level. Results: Females from urban areas (n = 2, 938, 991 [ie, total of females living in urban areas]) had a higher chance for predefined accessibility to the majority of analyzed facilities in comparison with females from rural areas (n = 3, 385, 813 [ie, total number of females living in rural areas]) with an odds ratio (OR) of 9.0 for cancer information counselling, an OR of 17.2 for a university hospital, and an OR of 7.2 for a psycho‐oncologist. For (inpatient) rehabilitation centers (OR, 0.2) and genetic counselling (OR, 0.3), women from urban areas had lower odds of accessibility within 30 or 60 minutes. Conclusions: Disparities in accessibility between rural and urban areas exist in Bavaria. The identification of underserved areas can help to inform policymakers about disparities in comprehensive health care. Future strategies are needed to deliver high‐quality health care to all inhabitants, regardless of residence. Abstract : Accessibility to evidence‐based structures for breast cancer care should be provided for all inhabitants, regardless of residence. Underserved regions and populations exist in the mainly rural state of Bavaria, Germany, and strategies to overcome these hurdles need integrated care forms as well as interventions by policymakers.